دراسة بعض الخصائص التقنية للمركب الآلي لزراعة الشعير عند مستويات مختلفة من السرع والحراثة الدنيا والصفرية. (Latakia University Journal -Biological Sciences Series, 2014)
تم إجراء التجربة في مركز البحوث العلمية الزراعية في السلمية التابعة لمحافظة حماه, في تربة لوميه طينية في تشرين الأول عام 2010م. استخدم في تنفيذ التجربة جرار الفرات مزود بمشط قرصي مفرد محمول كوحدة مكننة, للحراثة على ثلاث سرعات مرة واحدة للنظم المطلوب حراثتها وجه واحد, ومرتين للنظم المطلوب حراثتها وجهين, وبعدها جرت الزراعة بآلة التسطير. فيما خصصت أرض دون حراثة لنظام الزراعة الحافظة. تمت دراسة تأثير كل من الزراعة الحافظة وسرعة وتكرار الحراثة في النسبة المئوية للانزلاق, الإنتاجية الحقلية الفعلية, الكفاءة الحقلية, معدل مصروف الوقود والعمل المطلوب, وذلك من خلال نظم الحراثة والزراعة التالية: ن1: حراثة وجه واحد بالمشط القرصي المفرد بسرعة 5.07 Km/h, وزراعة بآلة التسطير بسرعة 9.97  Km/h. ن2:حراثة وجه واحد بالمشط القرصي المفرد بسرعة 7.47 Km/h, وزراعة بآلة التسطير بسرعة 10.08 Km/h. ن3: حراثة وجه واحد بالمشط القرصي المفرد بسرعة 9.77 Km/h, وزراعة بآلة التسطير بسرعة 10 Km/h. ن4: حراثة وجهين بالمشط القرصي المفرد بسرعة 5.21 Km/h, وزراعة بآلة التسطير بسرعة 10.09 Km/h. ن5: حراثة وجهين بالمشط القرصي المفرد بسرعة 7.71 Km/h, وزراعة بآلة التسطير بسرعة 10.10 Km/h. ن6: حراثة وجهين بالمشط القرصي المفرد بسرعة 10.16 Km/h, وزراعة بآلة التسطير بسرعة 10.12 Km/h. ن7: زراعة حافظة(دون حراثة ) بآلة مخصصة للزراعة على أرض غير محروثة بسرعة Km/h 7.25 .أظهرت النتائج أن زيادة سرعة الحراثة أدت إلى زيادة في النسبة المئوية للانزلاق وإلى زيادة في الإنتاجية الفعلية وانخفاض في الكفاءة الحقلية وفي مصروف الوقود. حيث سجل النظام N3 أعلى معدل للإنتاجية الفعلية 1.76 ha/h, وأقل معدل للكفاءة الحقلية 75%, وأقل معدل لمصروف الوقود 3.12  L/ha بالنسبة للحراثة, و5.79 L/ha خلال الحراثة والزراعة. كما تبين أن النظام N7 تطلب أقصر زمن 2932.43 s/ha, وأقل معدل لمصروف للوقود 3.43 L/ha, بنسبتي انخفاض مقدارهما على التوالي 68% -67%, وبالتالي تطلب أقل معدل من العمل اللازم 91.20 MJ/ha.  بينما تطلب النظام N4 أطول زمن 9093.13 s/ha, وأكبر مصروف وقود 10.59 L/ha, وكان العمل المطلوب 409.88 MJ/ ha. لذا نوصي بإتباع نظام الزراعة الحافظة للحصول على مؤشرات فنية أفضل.The experiment was conducted at the Agricultural Research Center in Salamiah in Hama province, in clay loam soil in October 2010. Furat tractor with a single hung disk harrow was used as a machinery unit, using three speeds. the seeding with drill seeder was executed after Applying  tillage one time for the systems required one face, and twice for the systems required two, while a plot of land was left for" zero tillage" system. the effect of " zero tillage", the speed and frequency of tillage on the sliding percentage, the actual productivity of field, field efficiency, fuel consumption rate and the work required, were studied through the following tillage systems and cultivation : N 1: tilling one face with single disc harrow at speed of 5.07 km / h , and seeding with drilling machine at speed of 9.97 km / h . N 2: tilling one face with single disc harrow at speed of 7.47 km / h , and seeding with drilling machine at speed of 10.08 km / h . N 3 : tilling one face with single disc harrow at speed of 9.77 km / h , and seeding with drilling machine at speed of 10.00 km / h . N 4 : plowing twice with single disk harrow at speed 5.21 km / h , and seeding with drilling machine at speed 10.09 km / h . N 5 : plowing twice with single disk harrow at speed 7.71 km / h , and seeding with drilling machine at speed 10.10 km / h N 6 : plowing twice with single disk harrow at speed 10.16 km / h , and seeding with drilling machine at speed 10.12 km / h N 7 : " zero tillage"  ( no-tillage ) by a machine dedicated for conservative agriculture on non cultivated land at speed  7.25 km / h . The results showed that an increase in the speed of tillage led to an increase in the sliding wheel and field productivity, and to a decrease in the field efficiency and fuel consumption, as system N3 achieved as for tillage the highest rate for actual productivity 1.76 ha/ h, and the lowest rate of  field efficiency 75%,  and of fuel consumption amounted to 3.12 l/ha, and achieved 5.79 l/ha for both tillage and seeding. As it is found that system N7 need the shortest time 2932.43  s/ha, and less fuel consumption 3.43 L/ha , equal to two percentages of reduction 68% -67 % respectively, and thus required minimum rate of required work 91.20 MJ/ha. While system N4 need the longest time of about 9093.13 s/ha, and consumed the largest amount of fuel 10.59 L/ha. The required work was 409.88 MJ/ ha. So we recommend to follow "zero tillage" system to get best technical characteristics.